Strategi Guru IPS dalam Meningkatkan Semangat Belajar Siswa Kelas VII pada Mata Pelajaran Ilmu Pengetahuan Sosial Melalui Metode Ice Breaking di SMP PGRI Bakung - Adimas Wijang Guritno; Dita Hendriani (Universitas 45 Surabaya, 2024)
Teacher strategy is a form of effort in learning, including varying how to deliver, teach and create an atmosphere to students. The ice breaking method or in Indonesian icebreaker is a model and game activity with the aim of breaking the ice. While the spirit of learning is a positive feeling that influences and changes behavior in an effort to obtain knowledge. In this strategy, the teacher provides ice breaking activities in class during the teaching and learning process to students with the aim of creating an active and eager classroom atmosphere. In this study using descriptive qualitative methods with a type of case study research. The data collection techniques are in the form of interviews, observations and documentation. The purpose of this study is 1) to determine the process of teacher strategies using the ice breaking method, 2) to find out the obstacles and support experienced by teachers in using the ice breaking method, 3) To find out the response of students in receiving the ice breaking method from the teacher. After the data collected data and data analysis, the results of the research in the form of using the ice breaking method in social studies learning were able to create an active classroom atmosphere and increase students' positive feelings in the form of enthusiasm for learning.